COMPARISON ANALYSIS OF LQ-45 SHARE PRICES BEFORE AND DURING THE COVID-19 PANDEMIC - Gabrilia, Filia; Octavia, Anita Dwi; Meliala, Melinda S; Sumaiya, Annisa (Universitas Mercu Buana, 2022)
The COVID-19 pandemic has impacted the world of capital markets, especially in LQ45. The company's share price globally, the Indonesian state, also experienced an unprecedented decline. The purpose of this study is to analyze the impact of the COVID-19 pandemic on LQ45 shares by comparing the average price of LQ45 shares before and after the COVID-19 pandemic in Indonesia. This study uses IBM SPSS Version 22 with a different pair-sample test model (compare means paired sample t-test). The results of this study indicate that the decline in stock prices in LQ45 shares before and after the COVID-19 pandemic reached Rp1,234.76.